PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KEDISIPLINAN GURU DI SMA NEGERI 1 TOBADAK KABUPATEN MAMUJU TENGAH - Syarifa Zaskia; Saepudin Mashuri; Irawanhadi Patanggu (STKIP Subang, 2026)
This study aims to determine the effect of the principal's leadership on teacher discipline at SMA Negeri 1 Tobadak, Central Mamuju Regency. The background of this study is the finding of several discipline problems among teachers, such as late arrival to class and incomplete preparation of learning tools, which are presumed to be related to the effectiveness of the principal's leadership. This study used a quantitative associative approach involving 35 teachers as respondents, determined through a saturated sampling technique. Data were collected using a Likert-scale questionnaire for the leadership variable (X) and the teacher discipline variable (Y), which had been tested for validity and reliability. Data were analyzed using classical assumption tests (normality and linearity) and simple linear regression with the help of SPSS. The results show that the data are normally distributed and linear, with the regression equation Y = 52.080 + 0.411X. The t-test shows t-count (2.474) > t-table (2.035) with a significance value of 0.019 < 0.05, indicating that the principal's leadership has a positive and significant effect on teacher discipline. The coefficient of determination shows that the principal's leadership explains 15.6% of the variance in teacher discipline, while the remaining 84.4% is influenced by other factors outside this study